Combustion of Fuel Mixtures Containing Crude Glycerol (CG): Important Role of Interactions between CG and Fuel Components in Particulate Matter Emission - Feng, Chao; Zhang, Mingming; Wu, Hongwei (American Chemical Society, 2018)
The paper reports an investigation into the effect of interactions among fuel components on the emission of particulate matter with aerodynamic diameter of <10 µm (PM10) during the combustion of fuel mixtures containing a formulated crude glycerol (CG) in air at 1400 °C. The experimental program considers four fuel components, that is, bio-oil, water-soluble fraction of bio-oil (WSF), biochar, and CG, two fuel blends, that is, bio-oil/methanol/CG blend (BMCG) and WSF/CG blend (WSFCG), and four slurry fuels, that is, bio-oil/biochar slurry (BB), WSF/biochar slurry (WSFB), BMCG/biochar slurry (BMCGB), and WSFCG/biochar slurry (WSFCGB). The results show that PM10 from the combustion of CG-containing fuel blends (i.e., BMCG and WSFCG) have unimodal distributions with a fine mode at ~0.043 µm. Therefore, the PM10 are dominantly PM1, which contributes to ~88.2 and ~99.3% of the total PM10 during the combustion of BMCG and WSFCG, respectively. However, the combustion of CG-containing slurry fuels (i.e., BMCGB or WSFCGB) produces PM10 having bimodal distributions with a fine mode at ~0.022 µm and a coarse mode at ~2.438 µm. The introduction of biochar increases the contribution of PM1–10 to the total PM10 from ~11.8 and ~0.7% for BMCG and WSFCG to ~53.1 and ~8.4% for BMCGB and WSFCGB, respectively. For CG-containing fuel blends, the interactions between CG and other fuel components result in enhanced chlorination of volatile inorganic species due to the abundant Cl originated from CG, leading to increasing emissions of these species in PM1. For CG-containing slurry fuels, such enhanced chlorination also takes place for both volatile and refractory inorganic species in biochar, leading to increasing emission of both volatile and refractory inorganic species in PM1 and decreasing emission of refractory inorganic species in PM1–10.